Acute Exercise Increases Adiponectin Levels in Abdominally Obese Men. (30th May 2012) - Saunders, Travis J.; Palombella, Andrew; McGuire, K. Ashlee; Janiszewski, Peter M.; Després, Jean-Pierre; Ross, Robert
Abstract : Objective . To examine the effect of acute and short-term (~1 week) aerobic exercise training on plasma adiponectin levels in inactive, abdominally obese men. Materials and Methods . Inactive and abdominally obese men (n = 38, waist circumference ≥102 cm) recruited from Kingston, Canada were randomly allocated to perform three bouts of aerobic treadmill exercise at either low (50% VO2 peak) or high (75% VO2 peak) intensity during a 1-week period. Blood samples were taken before and after the first exercise session and 24–72 hours following the completion of the final exercise session. Results . Adiponectin levels were elevated immediately following an acute bout of exercise at both high and low intensities (High: 5.79 ± 0.42 versus 5.05 ± 0.41  ug/mL; Low: 5 .24 ± 0 .44 versus 4 .37 ± 0 .44  ug/mL, P < 0.05 ) and remained elevated following 30 minutes of rest. In comparison to baseline, adiponectin levels were also elevated 24–72 hours following the final exercise session (High: 5.47 ± 0.48 versus 4.88 ± 0.48  ug/mL; Low: 5.18 ± 0.49 versus 4.47 ± 0.49  ug/mL, P < 0.05 ). Conclusion . Both acute and short-term aerobic exercise result in a significant increase in plasma adiponectin levels in inactive, abdominally obese men independent of intensity.